MOLECULAR BIOLOGY APPLIED TO THE FORENSIC AREA: A RESCUE IN TIME - Pereira Cavalheiro, Alesson (Journal of Interdisciplinary Debates, 2024)
The analysis of DNA samples to solve crimes is something widely oberved in films and fiction series, however, does this really happen in everyday life? The present work consists of a bibliographical review, the objective of which is to provide a historical review of the development of Molecular Biology, its use in the forensic field and the main techniques used by it. In this sense, it is noted that the development of this science, as well as the techniques and methodologies it carries out, accompany the technological development and tools available to it. The use of DNA, which once began with the aim of identifying immigrants, is now used in a variety of techniques to blame or discriminate against criminal suspects. Although it is advanced and this work describes some of the techniques used by molecular biology, many others can be characterized to understand the future of this science within criminal investigation.